THE COMPREHENSIVE SYSTEMATIC REVIEW OF RECURRENT EPISTAXIS - Jannah, Tania; Khaeriyah, Fie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Epistaxis affects roughly 60 of adults at some point in their lives, yet only about 10 necessitate medical intervention. Recurrent epistaxis remains a frequent reason for emergency department visits and involves multiple risk factors. This study aims to systematically review the literatures on recurrent epistaxis in the last 10 years. Methods: This systematic review adhered to the PRISMA 2020 standards and included full-text English literature published between 2014 and 2024. Exclusion criteria involved editorials, review articles from the same journal, and submissions lacking a DOI. Literature was gathered from online sources such as PubMed and SagePub. Result: Our search in PubMed yielded 76 articles, while SagePub produced 2415 articles. Focusing on the last 10 years (2014-2024), PubMed had 57 articles and SagePub had 712 articles. Ultimately we selected 6 papers that met our criteria, 3 from PubMed and 3 from SagePub. Conclusion: Managing recurrent epistaxis requires detailed examination on risk factors and underlying etiologies. The risk factors for recurrent epistaxis were unidentified bleeding point, blood parameters, the use of antithrombotic agent, and hereditary diseases. The current treatment of recurrent epistaxist can be done with bipolar cauterization and microwave ablation on bleeding points.